1992
DOI: 10.1038/jcbfm.1992.93
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Development of Ischemic Brain Edema in Vasopressin-Deficient Rats

Abstract: Summary: Brain edema formation was investigated in the vasopressin-deficient Brattleboro rat using a middle cere bral artery occlusion model of early ischemic injury. Wa ter and sodium accumulation after 4 h of ischemia were attenuated 36 and 20%, respectively, in the Brattleboro strain as compared to the control Long-Evans strain. This effect was independent of differences in animal size and state of hydration. In addition, measurements of ce rebral blood flow indicated that Brattleboro and Long Evans rats ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…1. Our previous studies have shown that the cerebral blood flow is reduced in the isch emic cortex to -20% of normal in this sample (Martz et aI., 1990;Dickinson and Betz, 1992). Validation of the use of the contralateral tissue as control has been presented previously (Menzies et aI., 1993).…”
Section: Meao and Brain Samplingsupporting
confidence: 70%
See 4 more Smart Citations
“…1. Our previous studies have shown that the cerebral blood flow is reduced in the isch emic cortex to -20% of normal in this sample (Martz et aI., 1990;Dickinson and Betz, 1992). Validation of the use of the contralateral tissue as control has been presented previously (Menzies et aI., 1993).…”
Section: Meao and Brain Samplingsupporting
confidence: 70%
“…Since the Kj values measured in this study were <5% of the rate of blood flow that we reported previously (Martz et ai., 1990;Dickinson and Betz, 1992), the Kj values are essentially identical to permeability-surface area (PS) products (Fenstermacher et aI., 1981). The PS product is influenced not only by the BBB permeability (P) of a substance but also by the amount of vascular surface (S) to which it is exposed.…”
Section: Measurement Of Brain Water and Ion Concentrationsmentioning
confidence: 84%
See 3 more Smart Citations